Organoleptic Test of Salted Eggs with Addition of Herbal Plants - Nur'aini, Nur'aini; Suningsih, Nining; Hakim, Muhammad (Indonesian Journal of Agricultural Research, 2020)
The addition of salt and herbal plants such as bay leaf (Eugenia polyantha) and lemongrass (Cymbopogon citratus DC) extacts can extender the shelf life and increase the flavor of the salted eggs. The purpose of this study was to determine the quality of eggs produced from using the herbal plants in terms of the organoleptic testing. This research used eggs from laying hens with salted egg making media consisting of rubbing ash plus salt, supplemented with bay leaf (Eugenia polyantha), lemongrass (Cymbopogon citratus DC), with storage period of 10 days. Organoleptic test results showed that the addition of bay leaves and lemongrass to the production of salted eggs, did not significantly improve the quality of salted eggs produced. The lack of storage time in the egg marinating process led to the incomplete, in salt water absorption into the egg. It is concluded that the addition of bay leaves and lemongrass to the media of making salted chicken eggs did not have a significantly different effect on the organoleptic quality of the salted eggs.